2017
DOI: 10.1021/acsami.7b05131
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Surfaces Modified with Carboxymethylthio Ligands for Chelate-Assisted Trapping of Copper

Abstract: The metal ion chelating property was conferred onto silicon (Si) and gold (Au) surfaces by direct electrografting of the 4-[(carboxymethyl)thio]benzenediazonium cation (4-CMTBD). Infrared spectroscopic ellipsometry showed the presence of characteristic phenyl and carbonyl vibrational bands on the functionalized surfaces as a proof of existence of surface-bound organic units of 4-[(carboxymethyl)thio]benzene, (4-CMTB). The loss of diazonium group (N≡N) upon electrografting of 4-CMTBD was investigated using IR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As shown in Figure 2d, a pair of double peaks at 105.1 and 101.2 eV are ascribed to Hg 4f 5/2 and Hg 4f 7/2 in the high-resolution XPS spectra, respectively. 37 Another pair of double peaks at 933.8 and 954.0 eV can be attributed to Cu 2p 3/2 and Cu 2p 1/2 , respectively, 38 accompanied by two satellite peaks at 939.1 and 943.1 eV. These indicate that adsorptions of the two metal ions occur on the surface of POFct-1.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure 2d, a pair of double peaks at 105.1 and 101.2 eV are ascribed to Hg 4f 5/2 and Hg 4f 7/2 in the high-resolution XPS spectra, respectively. 37 Another pair of double peaks at 933.8 and 954.0 eV can be attributed to Cu 2p 3/2 and Cu 2p 1/2 , respectively, 38 accompanied by two satellite peaks at 939.1 and 943.1 eV. These indicate that adsorptions of the two metal ions occur on the surface of POFct-1.…”
Section: Resultsmentioning
confidence: 92%
“…71,72 In addition, the emergence of two distinct peaks in the Cu 2p XPS core level spectrum positioned at 934.56 and 954.04 eV were attributed to Cu 2p 3/2 and Cu 2p 1/2 respectively, along with the shake-up satellite peaks at 943.65 and 963.70 eV, authenticating the presence of copper in its +2 oxidation state. 73,74…”
Section: Resultsmentioning
confidence: 99%
“…For macro–meso-TiO 2 , the elements Ti, O, and C appeared in the wide-scan XPS spectrum (Figure S10a), and the Ti 2p spectrum (Figure S10b) showed that the specific peaks of Ti 2p 3/2 and Ti 2p 1/2 occurred at 464.3 and 458.6 eV, respectively, indicating the existence of Ti 4+ in macro–meso-TiO 2 . For pure Cu-BDC, the elements Cu, O, and C emerged in the wide-scan XPS spectrum (Figure S10c), and the main spectrum occurred at 954.5, 934.6, and 943.5 eV (Figure S10d), which assigned to the Cu 2p 1/2 , Cu 2p 3/2 , and typical satellite, respectively, indicating that the oxidation state of Cu in pure Cu-BDC was Cu 2+ . To investigate whether the element state changed after the combination of macro–meso-TiO 2 and Cu-BDC, we further performed XPS analysis on Cu-BDC@macro–meso-TiO 2 .…”
Section: Resultsmentioning
confidence: 99%